Association of metabolic syndrome with neuroimaging and cognitive outcomes in the UK Biobank - Qureshi, D; Topiwala, A; Al Abid, S; Allen, N; Kuźma, E; Littlejohns, T (American Diabetes Association, 2024)
Objective: Metabolic syndrome (MetS) has been previously linked to dementia. This study examines the association of MetS with neuroimaging and cognition in dementia-free adults, offering insight into the impact of MetS on brain health prior to dementia onset. Research Design and Methods: We included 37,395 dementia-free adults from the UK Biobank. MetS was defined as ≥3 of the following components: elevated waistcircumference, triglycerides, blood-pressure, HbA1c, or reduced HDL-cholesterol. Multivariable-adjusted linear regression was used to assess associations of MetS with structural neuroimaging and cognitive domains. Results: MetS was associated with lower total brain (Standardised Beta-coefficient (β): - 0.06, 95%CI: -0.08, -0.04), grey matter (β: -0.10, 95%CI: -0.12, -0.08) and hippocampal volumes (Left-β: -0.03, 95%CI: -0.05, -0.01; Right-β: -0.04, 95%CI: -0.07, -0.02), and greater white matter hyperintensities (WMH) volume (β: 0.08, 95%CI: 0.06, 0.11). MetS participants performed poorer on cognitive tests of working memory (β: -0.10, 95%CI: -0.13, -0.07), verbal-declarative memory (β: -0.08, 95%CI: -0.11, -0.05), processing speed (β: -0.06, 95%CI: -0.09, -0.04), verbal and numerical reasoning (β: -0.07, 95%CI: -0.09, -0.04), nonverbal reasoning (β: -0.03, 95%CI: -0.05, -0.01), and on executive function, where higher scores indicated poorer performance (β: 0.05, 95%CI: 0.03, 0.08). An increasing number of MetS components were also associated with lower brain volumes, greater WMH, and poorer cognition across all domains. Conclusions: MetS was associated poorer brain health in dementia-free adults, characterised by lower brain volumes, greater vascular pathology, and poorer cognition. Further research is necessary to understand whether reversal or improvement of MetS can improve brain health.